A produção de energia elétrica com células de gás hidrogênio: perspectiva para o ensino de física - Pansera Júnior, Necleto (2019)
The teaching of physics in basic education has as one of its goals, to broaden in students the understanding they have about the world around them, making it possible to break with knowledge acquired outside the school environment. It also seeks to provide students with the acquisition of conceptual elements t hat allow the understanding and/or handling of technological devices. In this sense, the present investigation starts from the need to teach the content of electric energy production with hydrogen fuel cells in high school, since it has noways to didactically transpose such knowledge. This finding occurred through the analysis of the High School Physics textbooks provided by PNLD 2018 where only one of the ten books evaluated presented the form the production of electricity through hydrogen fuel cells. Also, through researches in the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel (CAPES), it was found that this theme did not exist in research work in the major areas of Education and Education. In this sense, the following question arises that guided this work: What competences and skills associated with Physics Teaching can be favored by approaching the hydrogen theme for the production of fuel cell electric energy? To answer this question, we take as reference the didactic transposition proposed by Yves Chevallard (2005) and the concept of competences of Philippe Perrenoud (1999). The aim of this study was to select and apply activities aimed at discussing the use of hydrogen fuel cells in the teaching of physics based on the development of competences and skills. For the development of the research, a sequence of activities was structured addressing the theme: “Production of electricity with hydr ogen fuel cells”. This study is structured based on didactic transposition and with the intention to develop and improve students' skills, supported by constructivism. The research assumes the qualitative and participatory approach, involving the productio n of data from the records of the teacher / researcher in the form of logbook and the students' response in the questionnaires applied before and after didactic intervention. The results show that the sequence of activities was favorable to the constructio n and development of competences and skills. The educational product that accompanies this dissertation refers to a website made for high school physics teachers and which gathers the activities developed during the didactic intervention.